2018
DOI: 10.3390/nano8080614
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CdTe Nanocrystal/TiO2 Hetero-Junction Solar Cells with Open Circuit Voltage Breaking 0.8 V by Incorporating A Thin Layer of CdS Nanocrystal

Abstract: Nanocrystal solar cells (NCs) allow for large scale solution processing under ambient conditions, permitting a promising approach for low-cost photovoltaic products. Although an up to 10% power conversion efficiency (PCE) has been realized with the development of device fabrication technologies, the open circuit voltage (Voc) of CdTe NC solar cells has stagnated below 0.7 V, which is significantly lower than most CdTe thin film solar cells fabricated by vacuum technology (around 0.8 V~0.9 V). To further improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In these structures, the quantum confinement effects control the properties of the materials with a dramatic change in their properties by varying the size of the nanocrystallite [1,2]. This behavior awards the semiconductor nanostructures and corroborates different applications such as photovoltaics [3,4,5], photocatalysis [6,7,8], lasers [9], transistors [10], biological labels [11], and light emitting devices [12,13]. The tunable physical and optical properties of semiconductor nanostructures can be achieved by two ways: the first by changing the size and dimension of the nanocrystals in the range below the exciton Bohr diameter; and the second is the variation of the optical and physical properties of the nanocrystallite by regulating the constituent stoichiometries of the alloy compounds.…”
Section: Introductionmentioning
confidence: 92%
“…In these structures, the quantum confinement effects control the properties of the materials with a dramatic change in their properties by varying the size of the nanocrystallite [1,2]. This behavior awards the semiconductor nanostructures and corroborates different applications such as photovoltaics [3,4,5], photocatalysis [6,7,8], lasers [9], transistors [10], biological labels [11], and light emitting devices [12,13]. The tunable physical and optical properties of semiconductor nanostructures can be achieved by two ways: the first by changing the size and dimension of the nanocrystals in the range below the exciton Bohr diameter; and the second is the variation of the optical and physical properties of the nanocrystallite by regulating the constituent stoichiometries of the alloy compounds.…”
Section: Introductionmentioning
confidence: 92%
“…The band gap of the material is also correlated with the thickness of the p-CdTe layer, which decreases with increasing thickness. The band gap of the p-CdTe material plays a vital role in enhancing the photovoltaic properties, absorption ability, and lifetime of carriers [29], [30], [31]. The impact of band gap alteration on the PCE of modulated heterojunctions was investigated in this work.…”
Section: Effect Of Band Gap Variation Of Absorber Layer (P-cdte) Sola...mentioning
confidence: 99%
“…Their devices showed enhanced electron mobility and a tunable Fermi level, which resulted in relatively low series resistance and improved PCE. In our previous work [ 36 ], we found that the performance of CdTe nanocrystal (NC) solar cells with an inverted structure of FTO/TiO 2 /CdTe/Au can be largely improved by inserting a thin layer of solution-processed CdS NC film between the CdTe NC and TiO 2 due to the optimized band alignment and p-n junction quality. The light absorption of the ETLs, however, might also negatively influence the device performance.…”
Section: Introductionmentioning
confidence: 99%